Odpowiedź :
Odpowiedź:
Szczegółowe wyjaśnienie:
Związki miarowe w trójkącie prostokątnym:
(h - 2)/b = b/(h - 2 + h + 3) to (h - 2)/b = b/(2h + 1) to (h - 2)(2h + 1) = b²
to 2h² - 4h + h - 2 = b² to 2h² - 3h - 2 = b² oraz z tw. Pitagorasa:
h² + (h - 2)² = b² to h² + h² - 4h + 4 = b² to 2h² - 4h + 4 = b² to
2h² - 3h - 2 = 2h² - 4h + 4 to - 3h - 2 = - 4h + 4 to h = 6
to b² = 6² + 4² = 36 + 16 = 52 = 4∙13 to b = 2√13
a² = 6² + 9² = 36 + 81 = 117 = 9∙13 to a = 3√13 oraz c = 4 + 9 = 13
to: Odpowiedź:
Obwód tego trójkąta jest równy:
a + b + c = 3√13 + 2√13 + 13 = 5√13 + 13